ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL PADA MASA KRISIS EKONOMI GLOBAL: ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL PADA MASA KRISIS EKONOMI GLOBAL - Achmad Zubairi; yusril haza (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
This study aims to perform acomparative analysis of financial performance between Islamic banks and conventional banks during the global economic crisis. This study was conducted to provide a deeper understanding of how these banks performed during the crisis period and to compare the strengths and weaknesses of the two. Quantitative methods are used by analyzing public financial data related to Islamic banks and conventional banks in Indonesia. The results of this study are expected to provide useful insights for practitioners, regulators and decision makers in the banking industry. The findings of this research can become the basis for developing more effective policies in dealing with future economic crises.